(untitled) (Studia Prawnicze / The Legal Studies, 1985)
Referring to descriptionistic and reconstructionistic analysis of language accepted in semiotic literature the article shows that in fact descriptionistic analysis has not been widely applied, as it leads to unfruitful conclusions in case of linguistic confusion in a certain sphere of jurisprudence, which is a common phenomenon. In the development of research on law it is necessary to introduce new theoretical terms into legal language, which is beyond the interests of descriptionists. Moderate but not radical and arbitrary reconstructionism is useful here.